STF e CrIDH : anistia dos crimes por motivação política no período da ditadura militar - Montenegro, Caroline Alves (2014)
The Brazilian military dictatorship in 1964 was a period of terrible crimes against human beings and their democratic freedom, nationally, against those who were considered threats to the system of political, social, economic and cultural repression, or it is, to those who advocated or communed with socialist and communist ideas. At that time there was the installation of the military dictatorship of the right in the South America rights. Our country has some belated measures related to the transition process. The 1979 law, despite being considered the first step towards democratization of the country, has numerous flaws because of the strong military imposition. One aspect of Brazilian transitional justice which characterizes it, is to repair this recognition with respect to political persecution and not to the torturers, beginning on CF/88 in Article 8º of the ADCT, among other subsequent legislative measures, such as reentry the previous function, the incorporation of time for social security, other remedies with the Commission of Truth and Memory, Caravan of Amnesty etc. Some changes are observed, however our country is considered as the one in the region, unlike Argentina, for example, to adopt a position not evolved with regard to amnesty for political crimes of the military dictatorship of the 1970s, without adequately analyzing the Inter-American Court jurisprudence from Chile, Peru and Uruguay, in the matters related to the topic. This research, therefore, focuses primarily on an analysis of the following points: the formation of European and Brazilian national states, the importance of democracy in the evolution of national and international studies on the protection of human rights, globalization as an important way for greater interdependence and connection among countries, the need to expand and strengthen the study of issues related to the Inter-American System, in particular, control of conventionality, especially after the 1990s, when many countries had ratified both the American Conventions, as the jurisdiction of Inter-American Court, the study of transitional justice in Brazil and the changes that occur from the law nº 6.683/79. From this analysis, we may seek to ultimately present the impact of case Gomes Lund vs. Brazil (2010), after the trial of ADPF nº 153 correlating it with other jurisprudence of Inter- American Court of Human Rights, as well as, decisions and judgments, including those of Peru (2001), Chile (2006) and Uruguay (2011).